Social Competence and Career Development: Validation of a Scale with Secondary Students (2015)
This paper presents a validation study of the Perceived Social Competence in Career Scale (SCCarS). The sample included 571 adolescents, 283 girls (49.6%) and 287 boys (50.3%), aged 14 to 25 years old (ì=16.33±1.41), 10th and 11th grade students attending secondary schools in the northern, central and southern Portugal. Exploratory factor analysis indicates the presence of eight factors, with eigenvalues superior to 1.00, explaining 79.16% of the total variance of the items. Confirmatory factor analysis provided support to the factorial structure of eight factors, with adequate fit indices (X2/df=4.229, CFI= 0.909, GFI= 0.869, RMSEA= 0.079, p= 0.000). These results are consistent with the factorial structure found in previous studies carried out with Portuguese samples from 8th grade. Implications are drawn related to the need for further study of the psychometric characteristics of the SCCarS with young people from different age groups.